Mediterranean Diet and Cardiovascular Risk: Beyond Traditional Risk Factors. Issue 5 (3rd April 2016) - Delgado-Lista, Javier; Perez-Martinez, Pablo; Garcia-Rios, Antonio; Perez-Caballero, Ana I.; Perez-Jimenez, Francisco; Lopez-Miranda, Jose
Abstract : A strict adherence to the Mediterranean Diet (MedDiet) has repeatedly been linked to a low risk of cardiovascular disease in several situations. Initially, the mechanisms considered as possible causes of this were based on the effects of this dietary pattern on the so-called traditional risk factors (especially lipids and blood pressure). However, the high relative reduction in the prevalence of cardiovascular morbidity and mortality were not proportional to the limited findings about regulation of those traditional risk factors. In addition to several studies confirming the above effects, current research on the MedDiet is being focused on defining its effects on non-traditional risk factors, such as endothelial function, inflammation, oxidative stress, or on controlling the conditions which predispose people to cardiovascular events, such as obesity, metabolic syndrome or type 2 diabetes mellitus. In the current article, after briefly reviewing the known effects of the MedDiet on the traditional risk factors, we will mainly focus on reviewing the current evidence about the effects that this dietary pattern exerts on alternative factors, including postprandial lipemia or coagulation, among others, as well as providing a short review on future directions.